E-Learning Courseware Usability: Building a Theoretical Model - Koohang, Alex; Paliszkiewicz, Joanna (The Journal of computer information systems, 2016)
Based on a stream of research, this study identified four components of the e-learning courseware usability: fundamental, appearance, information presentation, and communication. The communication component was considered an expanded component of the e-learning courseware usability. A theoretical model was built and three hypotheses were developed to examine whether the communication component as an expanded component of the e-learning courseware usability significantly and positively contributed to the three components of the e-learning courseware usability (fundamental, appearance, and information presentation). An instrument was developed and administered to subjects taking various e-learning courses. The collected data were analyzed using a variance-based Structural Equation Modeling (SEM) package that uses Partial Least Square (PLS). Analyses of the results indicated a strong validated model supporting all stated hypotheses.